Media Lagu dalam Meningkatkan Kosakata Bahasa Jerman - Nabila Inas Suhailah; Syamsu Rijal; Burhanuddin Burhanuddin (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This research is a class action research that consisted of two cycles. The aim of this research is to know the planning, the process and the outcome of the song to improve the vocabulary of the students XII MIPA 5 SMA Negeri 8 Makassar. The research data are quantitative and qualitative. The quantitative data from the tests in the first and second cycle and the qualitative data were collected from the observations and analyzed by the percentage technique. The results showed that the vocabulary proficiency was 69.5% in the first cycle and 85.5% in the second cycle and had reached the minimum completeness criteria value at SMA Negeri 8 Makassar with an average value of 75%. This means that the lied learning media for German vocabulary can improve the students XII MIPA 5 SMA Negeri 8 Makassar. Keywords: Song media, Vocabulary, German Language